Modeling and characterization of thin film and nanostructured perovskite and kesterite solar cells - Sara Youssef Abdelrahman Ahmed Abdelrahman; Nadia H. Rafat; Nouran M. Ali (2025)
This thesis investigates innovative approaches to enhance the performance of photovoltaic solar cells. A novel analytical model, for calculating the recombination rates and precise photocurrent determination, is developed for planar solar cells of short carrier lifetime materials. This model, validated against simulation and experimental data, precisely predicts J-V characteristics of kesterite-based photovoltaic cells. Nanostructured designs were proposed and simulated for environmentally friendly perovskite solar cells, showing a 33% reduction in toxic lead content while improving efficiency. In the non-toxic alternative, kesterite solar cells, introducing semi-ellipsoidal nanostructures significantly improves efficiency to 17.6%.
(3JHMK gPg GdQSGdI aj CSGdjH eHJcQI dJYRjR COGA GdNdGjG GdTeSjI GdcgQhVhFjI(B. (3dbO Je JWhjQ fehPL JMdjdj LOjO dMSGH eYOdGJ EYGOI GJMGO MGedGJ GdTMfI hJMOjO GdJjGQ GdVhFj HObI, hPdc ddNdGjG GdTeSjI GdeSWMI GdeUfhYI ef ehGO PGJ aJQI MjGI bUjQI dMGedGJ GdTMfI(B. (3jJfHC gPG GdfehPL, GdPj Je GdJMbb ef UMJg ebGHd HjGfGJ GdeMGcGI hGdHjGfGJ GdeYedjI, HObI HNUGFU GdLgO hGdJjGQ ddNdGjG GdcgQhVhFjI GdbGFeI Ydi GdcSJQGjJ(B.(3HGdEVGaI dPdc, Je GbJQGM heMGcGI gjGcd fGfheJQjI dNdGjG HjQhaScGjJ GdTeSjI GdUOjbI ddHjFI, eeG ojXgQ GfNaGkVG HfSHI (B33(3% aj eMJhi GdQUGU GdSGe eY JMSjf GdcaGAI(B. (3CeG aj NdGjG GdcSJQGjJ GdTeSjI, hgj GdHOjd ZjQ GdSGe, ajDOj EONGd GdgjGcd GdfGfheJQjI fUa GdHjVGhjI Edi JMSjf GdcaGAI HTcd cHjQ Edi (B17.6(3%(B.s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 85-99.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Physics; (3GdajRjGAs; Photovoltaics -- light trapping -- recombination -- TMM -- Power conversion efficiency